Growth and potential purification ability of Nitzschia sp. benthic diatoms in sea cucumber aquaculture wastewater. (24th May 2018) - Xing, Rong‐lian; Ma, Wei‐wei; Shao, Yi‐wen; Cao, Xue‐bin; Su, Chan; Song, Hong‐xu; Su, Qun; Zhou, Ge‐fei
Abstract: The growth patterns and water treatment capacity of Nitzschia sp. benthic diatoms in different concentrations of sea cucumber aquaculture wastewater (0%, 10%, 30%, 50%, 80% and 100%) and f/2 medium were studied. Nitzschia sp. grew in different concentrations of aquaculture wastewater and showed remarkable differences in their rate of growth among the treatment groups. Nitzschia sp. grew most quickly (0.83 ind/day) and showed the greatest total chlorophyll‐a content in 30% wastewater. The total chlorophyll‐a content and growth rate of Nitzschia sp. were strongly correlated ( R 2  > 0.98). The total lipid (TL), total protein, exopolysaccharide (EPS) and intracellular polysaccharide (IPS) contents of the diatoms were highest in 100% wastewater and showed significant differences among the experimental groups ( p  <   0.05). Total nitrogen (TN), ammonium‐nitrogen (NH4 ‐N) (AN), nitrate nitrogen (NO3 ‐N) (NN), nitrite nitrogen (NO2 ‐N) (NIN) and total phosphate (TP) contents were significantly reduced after cultivation. TN uptake peaked at 54.58% in 30% wastewater. AN uptake exceeded 95% in 30% wastewater and 100% wastewater. NN uptake peaked at 56.42% in 80% wastewater, whereas TP uptake ranged from 16.80% to 27.69%. These results suggest that Nitzschia sp. biomass can be enhanced via cultivation in low‐concentration (30%) wastewater, after which their cultivation may be continued in high‐concentration (100%) wastewater, increasing their nutritional value and aiding in the removal of surplus nitrogen and phosphorus in sea cucumber aquaculture wastewater. Application of Nitzschia sp. using the recirculating wastewater‐treatment methods described has the potential to reduce environmental harm caused by sea cucumber cultivation and thus achieve sustainable aquaculture.